An effective disinfection protocol for the development of tissue culture mango plant (Mangifera indica L.) cv. Harumanis - Zun, Yip Lee; Amir Hamzah Ahmad Ghazali,; Bee, Lynn Chew; Sreeramanan Subramaniam, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Harumanis mango is one of the highest demand mango cultivars in Malaysia due to its exceptional sweetness and fabulous fragrance. However, the production of this mango cannot meet the market demand due to limited grafting activity and the limited number of seeds (only one harvest season per year). These make vegetative and non-vegetative propagation of Harumanis time and labour intensive. Micropropagation using tissue culture techniques is a reliable and effective alternative for mass in vitro propagation of Harumanis at a consistent and faster rate, producing clones of the mother plants. Nevertheless, deep-seated contaminants are the major problem faced in the micropropagation of this plant. The objective of the present study is to develop an effective disinfection protocol for Mangifera indica cv. Harumanis. A sterility rate of 87.5% was achieved by spraying the mother plants with 0.5 mL/L azoxystrobin two days before the experiment (pre-treatment) and surface sterilising nodal segments at the immature green leaf stage with 40% Clorox® for 20 min, 0.5 g/L benomyl for 1 hr and 300 mg/L cefotaxime for 5 min. The transverse thin layer (tTCL) technique was applied to the nodal segments and cultures were maintained at WPM with 0.5 g/L benomyl and 300 mg/L cefotaxime. Endophytic bacteria and fungi were observed in the axillary buds using scanning electron microscopy (SEM). Both histological and SEM analysis showed that the xylem vessels of the nodal segments at these two ends of the stem tended to have lower numbers of endophytic bacteria. This suggests that the nodal segments at the upper and middle ends of the stem are the best starting material for future experiments. The present results show the importance of pre-treatment and culture maintenance in reducing endophytic contamination. Furthermore, the results showed the potential of tTCL-treated Harumanis cultures in minimising the contamination rate.